The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1097/brs.0b013e3181ce8f4b
|View full text |Cite
|
Sign up to set email alerts
|

Bone Grafting Options in Children

Abstract: Although autogenous iliac bone graft remains the benchmark to which bone grafting materials are compared, other options including the placement of no bone graft at all provides similar fusion rates in patients with AIS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 35 publications
(21 reference statements)
0
31
0
Order By: Relevance
“…Several surgical techniques can be used, but it is essential to obtain solid arthrodesis at the operated segment [1][2][3][4][5]. Several surgical techniques can be used, but it is essential to obtain solid arthrodesis at the operated segment [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several surgical techniques can be used, but it is essential to obtain solid arthrodesis at the operated segment [1][2][3][4][5]. Several surgical techniques can be used, but it is essential to obtain solid arthrodesis at the operated segment [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Several surgical techniques can be used, but it is essential to obtain solid arthrodesis at the operated segment [1][2][3][4][5]. However, several complications are described at the donor site, especially pain [4,5,[8][9][10][11][12]. This type of graft is considered the gold standard for presenting excellent osteoconductive and osteoinductive properties, without the risk of disease transmission or immune reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to adult patients, there is significant morbidity associated with bone graft harvesting and up to 31 % of adolescent patients complain of persistent harvest site pain 2 years after surgery [57]. The reported success of bone graft substitutes in the adult spine literature has led to the use of rhBMP-2 in pediatric and adolescent patients.…”
Section: Bmp Utilization In Adolescentsmentioning
confidence: 99%
“…Although there are limited published reports, rhBMP-2 appears to be a safe and effective alternative to promote spinal fusion in a selective group of adolescent patients [57]. Fahim et al reported a 100 % fusion rate with rhBMP-2 in cervical, thoracic, and lumbar fusions after a mean 17-25 month follow-up [62].…”
Section: Argument In Favor Of Bmp Utilization In Adolescent Patientsmentioning
confidence: 99%
“…Several clinical studies have documented favorable results by using adult lumbar spine and anterior cervical spine models. 6,9 Although BMP has been used with some frequency in pediatric oral maxillofacial reconstructions 7,8,[13][14][15]18,26,56 and reported in the treatment of congenital pseudarthrosis of the tibia, 32,46 there have been few reports of rhBMP-2 use 1,4,20,36,37,40 in pediatric spine fusions. One recent study 31 of patients in the pediatric age group in the Nationwide Inpatient Sample database analyzed various factors associated with the use of BMP for specific diagnoses, including adolescent idiopathic scoliosis, Scheuermann kyphosis, congenital kyphosis, spondylolisthesis, and thoracolumbar fracture; procedures related to the occipitocervical and cervical spine were not included in this study.…”
mentioning
confidence: 99%